The Influence of Rural Population Density and Gross Agricultural Production on the Development of RA Rural Areas - Potosyan, Aksel; Potosyan, Vahan (Bulletin of Yerevan University G: Economics, 2021)
The economic development and progress of RA rural areas are conditioned by natural-geographical, agro-productive, socio-demographic, regional, and other interconnected factors.The article analyzes and evaluates the agro-production preconditions for the development of modern rural territories of the country and rural settlements as the main element. It also revealed current problems of rural areas and settlement pattern development procedures.
Keywords: rural areas; rural settlements; rural population density; development problems; gross agricultural production